PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA MATERI SISTEM PEREDARAN DARAH MEMANFAATKAN E-LEARNING BERBASIS EDMODO UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI - Maysharoh, Siti; Natalina L, Mariani; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of this research is to develop learning media with good quality in the circulatory system material utilizing e-learning based on edmodo to improve students learning motivation in XI class. Further, e-learning validity test based on edmodo as learning media. The research was conducted in campus of Biology Education Program of FKIP Universitas Riau, it start from June to October 2017 by using Research and Development (R&D) approach with ADDIE model. This research is only in the Development stage. Learning media that has been developed is in circulatory system meterial. The instrument has been used is edmodo based e-learning validation sheet that containing 24 questions and was filled by 5 validators. Furthermore, it was conducted first test to 13 students biology education semester 1 and second test to 19 students of grade XII SMA Negeri 1 Pekanbaru by using questionnaire of student response. Research data were analyzed using descriptive statistical analysis. The result of edmodo based e-learning validation on the circulation system material is seen from 4 aspects, display, program, learning and curriculum. The result of validation is strong valid with score 3.86. The results of the first trial on students are in very good category for media and LTPD are 100% and 92.3% respectively. The second trial result of the students was in very good category on media and LTPD were 95% and 50% respectively. The result of questionnaire of motivation to learn is in good category in trial I is 3.30 or as much as 82.40% and trial II is 3.24 or as much as 80.97%. Learning tools developed can be used as an alternative learning tool and to improve student motivation of class XI.Keywords: Edmodo Based E-Learning, Learning Tool, Questionnaire response, Validation Sheet.